Description Of Mother's Knowledge In Prevention And Acceleration Of Stunting Reduction In Mandiri Midwife Practices, Medan Helvetia District In 2022 - Nazri Nasution (Institute of Computer Science (IOCS), 2022)
The purpose of this research was to determine the level of mother's knowledge in stunting prevention efforts. This research used a descriptive methods with a retrospective approach and was conducts at the Midwifery Practice a Medan Helvetia District. The population in this research were pregnant mothers and mothers of toddlers (under 5 years old) at the Midwifery Practice for a period of six months (April 2022–August 2022). The sample of 35 respondents used a purposive sampling technique, namely the researcher determined the criteria for the samples taken. The method of data collection used is through direct interviews based on structured questionnaires with closed answers and data collection related to research objectives. Data categories include age, education level, occupation, and level of knowledge. Data analysis was performed using SPSS. The results showed that most of respondents were mothers who had toddlers (under 5 years old) as many as 21 respondents (60%), the dominant respondent's age was 26-35 years, namely 25 respondents (71.4%), the dominant education was higher education, as many as 14 respondents (40%), and the dominant occupation of housewives as many as 23 respondents (65.7%). The description of knowledge of pregnant mothers and mothers of toddlers (under 5 years old) is mostly in the poor category, as many as 15 respondents (42.9%). and the dominant occupation of housewives as many as 23 respondents (65.7%). The description of knowledge of pregnant mothers and mothers of toddlers (under 5 years old) is mostly in the poor category, as many as 15 respondents (42.9%). and the dominant occupation of housewives as many as 23 respondents (65.7%). The description of knowledge of pregnant mothers and mothers of toddlers (under 5 years old) is mostly in the poor category, as many as 15 respondents (42.9%).